Adherence to the tobacco-free educational institution guidelines at schools of Raipur Rani, Haryana - Amit Kumar; Arpit Gupta; Sonu Goel; Krishan Gauba; Ashima Goyal (Wolters Kluwer Medknow Publications, 2021)
Tobacco-Free Educational Institution (ToFEI) guidelines are required to be followed by the schools. This cross-sectional study conducted in the year 2019 assessed the accordance with ToFEI guidelines among all the 84 schools of Raipur Rani educational block, Haryana. Investigators collected data from all the government (71) and private (13) schools during school working days. Tobacco sales within 100 yards of the school premises was covertly observed. None of the schools thoroughly complied with the tobacco-free school policy, though the compliance score for private schools (26.77 ± 19.15) was better than the government schools (13.65 ± 4.38). Only two private schools achieved the mandatory score of 50. All private schools and few government schools (42.3%) had successfully implemented the ban on tobacco sale within 100 yards of the school. None of the schools could achieve a ToFEI status in the present study. The policymakers and implementers should prioritize ToFEI agenda & support schools in achieving tobacco-free status.